2005
DOI: 10.1074/jbc.m503499200
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Structural Consequences of Perturbing Gly-193 in theOxyanion Hole of SerineProteases

Abstract: The oxyanion hole of serine proteases is formed by the backbone N atoms of the catalytic Ser-195 and Gly-193 and engages the backbone O atom of the P1 residue of substrate in an important H-bonding interaction. The energetic contribution of this interaction in the ground and transition states is presently unknown. Measurements of the individual rate constants defining the catalytic mechanism of substrate hydrolysis for wild-type thrombin and trypsin and their G193A and G193P mutants reveal that Gly-193 is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
(43 reference statements)
5
33
1
1
Order By: Relevance
“…If the N143P mutant disrupts the oxyanion hole, as expected, then the energetic consequences do not abrogate activity altogether and depend on the particular enzyme-substrate complex formed. This is consistent with the results obtained with direct perturbation of Gly 193 (83) and studies on clotting factor VIIa where active site ligands were found to reconstitute the correct architecture of the oxyanion hole disrupted by the flip in the 192-193 peptide bond (50). Binding of thrombomodulin to exosite I of N143P does not ameliorate the energetic penalty on substrate recognition by the active site, even in the case of the anticoagulant substrate protein C. Although the data in Fig.…”
Section: Resultssupporting
confidence: 82%
“…If the N143P mutant disrupts the oxyanion hole, as expected, then the energetic consequences do not abrogate activity altogether and depend on the particular enzyme-substrate complex formed. This is consistent with the results obtained with direct perturbation of Gly 193 (83) and studies on clotting factor VIIa where active site ligands were found to reconstitute the correct architecture of the oxyanion hole disrupted by the flip in the 192-193 peptide bond (50). Binding of thrombomodulin to exosite I of N143P does not ameliorate the energetic penalty on substrate recognition by the active site, even in the case of the anticoagulant substrate protein C. Although the data in Fig.…”
Section: Resultssupporting
confidence: 82%
“…This may reflect the energy required to break interactions between the larger side chains of Asp, Val, Glu, and Lys and surrounding residues to allow rotation of the 192-193 bond so that the amide nitrogen of residue 193 points toward the oxyanion hole. In the case of Pro 193 , the residue lacks an amide nitrogen preventing its participation in hydrogen bonding with the oxyanion of the substrate/inhibitor (52). The effects of residue 193 side chains on FXIa activity should apply to proteases such as FVIIa and FIXa, which have similar hydrophobic S2′ sites (36)(37)(38)53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Functional Assays-Wild-type trypsin and tissue-type plasminogen activator were expressed, purified, and tested for activity as described (23,24). Chymotrypsin was from Sigma.…”
Section: Methodsmentioning
confidence: 99%